Live and let die: Hydrogen peroxide production by the commensal flora and its role in maintaining a symbiotic microbiome. (15th July 2018) - Redanz, Sylvio; Cheng, Xingqun; Giacaman, Rodrigo A.; Pfeifer, Carmen S.; Merritt, Justin; Kreth, Jens
Summary: The majority of commensal oral streptococci are able to generate hydrogen peroxide (H2 O2 ) during aerobic growth, which can diffuse through the cell membrane and inhibit competing species in close proximity. Competing H2 O2 production is mainly dependent upon the pyruvate oxidase SpxB, and to a lesser extent the lactate oxidase LctO, both of which are important for energy generation in aerobic environments. Several studies point to a broad impact of H2 O2 production in the oral environment, including a potential role in biofilm homeostasis, signaling, and interspecies interactions. Here, we summarize the current research regarding oral streptococcal H2 O2 generation, resistance mechanisms, and the ecological impact of H2 O2 production. We also discuss the potential therapeutic utility of H2 O2 for the prevention/treatment of dysbiotic diseases as well as its potential role as a biomarker of oral health.